Quality Assurance & Software Testing na empresa 4ALL Software - Alves, Diana dos Santos (2023)
It is extremely important that the information systems developed are subjected to a set of quality tests (software testing) to detect errors or failures and correct them, as well as to ensure that the final product meets the needs of the customer. The work in the company 4ALL Software consisted in ensuring the software quality of the Dominis platform before it was delivered to the customer. The main objective was to model the system, develop and apply software quality tests to the platform, using manual and automated tests. To meet the proposed objectives, preliminarily, the survey of functional and non-functional requirements was conducted, followed by its analysis. The system was then modelled using diagrams from the unified modeling language. A systematic review of the literature was performed to synthesize clear and objective information related to the topic of software quality assurance. The review aimed to answer questions such as: what is software quality assurance?; What is Software Testing and what are its goals?; What are the categories and levels of Software Testing? And what are the techniques used in software testing?; among other pertinent issues. Then, based on the requirements gathered earlier, test plans were developed that included unit-level, integration, system, and acceptance testing. The execution of these tests allowed to identify bugs that could compromise the efficiency of the platform. Unit-level testing was performed through Python scripts using the pytest test framework to evaluate the API. For the integration or system tests of the web and mobile applications, the Katalon Studio tool (automatic tests) was used and in certain cases, manual tests were performed. Acceptance tests were performed manually.